Attachment Style and Chronic Pain: Toward an Interpersonal Model of Pain - Romeo, Annunziata; Tesio, Valentina; Castelnuovo, Gianluca; Castelli, Lorys (Frontiers in Psychology, 2017)
Chronic pain (CP) is a burdensome symptom. Different psychological models have been proposed to explain the role of psychological and social factors in developing and maintaining CP. Attachment, for example, is a psychological construct of possible relevance in CP. The first studies on the role of attachment in CP did not investigate the partner’s psychological factors, thus neglecting the influence of the latter. The main aim of this mini-review was to examine the more recent literature investigating the relationship between CP and attachment style. In particular, whether or not more recent studies assessed the psychological variables of a patient’s partner. The articles were selected from the Medline/Pubmed database using the search terms “attachment” AND “pain”; “chronic pain” AND “attachment style”, which led to nine papers being identified. The results showed that, even though the key point was still the hypothesis that an insecure attachment style is associated with CP, in recent years researchers have focused on the possible psychological aspects mediating between attachment style and CP. In particular, worrying, coping strategies, catastrophizing and perceived spouse responses to pain behavior were taken into account. Only one study considered the role of the reciprocal influence of attachment style of both patient and partner, underlining the role of real significant others’ responses to pain behaviors. In conclusion, the results of the present mini-review highlight how in recent years researchers have moved towards investigating those psychological aspects that could mediate the relationship between attachment and CP, while only partially evaluating the interpersonal perspective.